HIV Through the Looking Glass: Insights Derived From Hepatitis B. (1st February 2015) - Rivera, Maria M.; Soza, Alejandro; Jazwinski, Alison; Mi, Lijun; Kleiner, David E.; Zhao, Xiongce; Zuber, Charma; Brust, Douglas; Hsu, Emory; Simpson, Jennifer; Hoofnagle, Jay H.; Heller, Theo
Abstract : Background: Although higher levels of hepatitis B virus (HBV) replication in HIV-HBV co-infection may relate to liver disease progression, this has not been completely elucidated. We used expression of hepatitis B core antigen (HBcAg) in liver biopsies from HIV-HBV co-infected and HBV mono-infected patients as a marker for HBV replication, and related these findings to clinical and histological parameters. Methods: Data from 244 HBV patients were compared with 34 HIV-HBV patients. Liver biopsies were scored for inflammation, fibrosis, HBcAg, and hepatitis B surface antigen. Univariate and multivariate analyses were performed. Results: HBcAg, but not hepatitis B surface antigen, staining was stronger in HIV co-infected than in HBV mono-infected. Co-infected and HBV mono-infected had similar alanine aminotransferase, inflammatory and fibrosis scores, and hepatitis B e antigen status. HBcAg staining correlated with HIV after correcting for HBV DNA and hepatitis B e antigen. CD4 counts and HIV RNA level did not correlate with intensity of HBcAg staining. HBV DNA levels were higher in HIV co-infected and correlated with HBcAg staining. Conclusions: By looking at HBcAg as a reflection of HBV replication in HIV-HBV co-infected with controlled HIV, our findings suggest that these patients may have subtle immune function defects, which could lead to adverse liver disease outcomes. Abstract : Supplemental Digital Content is Available in the Text.